LIKUIDITAS MEMODERASI PENGARUH PROFITABILTAS DAN INVESTMENT OPPORTUNITY SET (IOS) PADA KEBIJAKAN DIVIDEN - Ariandani, Putu Sri; Yadnyana, I Ketut (E-Jurnal Akuntansi, 2016)
This study aims to determine the effect of profitability on dividend policy, determine the effect of investment opportunity set on dividend policy, determine the effect of profitability on dividend policy with liquidity as moderating variable and determine the effect of investment opportunity set on dividend policy with liquidity as moderating variable. This study was performed on manufacturing companies listed in Indonesia Stock Exchange during the years 2012-2014. The sampling method that used is non-probability sampling with purposive sampling technique. Data collection method is a non-participant observation. Samples from this study as many as 30 companies. Data analysis technique is analysis moderate analysis (MRA). The results of the analysis show that profitability of positive and significant effect on dividend policy, IOS has no effect on dividend policy, liquidity can’t  moderate the effect of profitability on the dividend policy and liquidity can’t moderate effect of IOS on dividend policy.
Keywords: liquidity, profitability, investment opportunity set, dividend policy